1979
DOI: 10.1073/pnas.76.9.4385
|View full text |Cite
|
Sign up to set email alerts
|

Subunit structure of dihydrolipoyl transacetylase component of pyruvate dehydrogenase complex from Escherichia coli

Abstract: Limited tryptic digestion of the pyruvate dehydrogenase complex of Escherichia coli or its dihydrolipoyl transacetylase core cleaves the trypsin-sensitive transacetylase subunits into two large fragments, A (lipoyl domain) The pyruvate dehydrogenase complex from Escherichia coli is organized about a core, consisting of dihydrolipoyl transacetylase, to which pyruvate dehydrogenase and dihydrolipoyl dehydrogenase are joined by noncovalent bonds (1). The appearance of the transacetylase in the electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 26 publications
7
73
0
Order By: Relevance
“…The subunits of dihydrolipoamide acyltransferases from other organisms typically of one to three lipoyl-binding domain and one catalytic domain, which are connected through proteasesensitive hinge regions (5,9,20,28,40). Upon limited proteolysis under nondenaturing conditions, the hinge regions are cut and usually two fragments with similar molecular masses, representing the lipoyl-binding domains and the catalytic domain, were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subunits of dihydrolipoamide acyltransferases from other organisms typically of one to three lipoyl-binding domain and one catalytic domain, which are connected through proteasesensitive hinge regions (5,9,20,28,40). Upon limited proteolysis under nondenaturing conditions, the hinge regions are cut and usually two fragments with similar molecular masses, representing the lipoyl-binding domains and the catalytic domain, were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Dihydrolipoamide acyltransferases (E2 components) of 2-oxo acid dehydrogenase complexes from different sources are very sensitive to proteolytic cleavage under nondenaturing conditions (5,9,20,28,40). After limited proteolysis, a domain comprising the lipoyl moieties (designated the lipoylbinding domain) and a domain containing the acetyltransferase activity (designated the catalytic or subunit-binding domain) are usually obtained.…”
Section: Downloaded Frommentioning
confidence: 99%
“…On the basis of their susceptibility to limited proteolysis [1,3,31] and their identification as the origin of many of the unexpectedly sharp signals detected by 1H-NMR spectroscopy [10][11][12][13], the long (alanine + proline)-rich segments of the E. coli E2p chain are thought to be exposed to solvent and conformationally flexible. Perhaps it is not so surprising, therefore, that peptide PEP3 is strongly immunogenic and that the anti-PEP3 Fab fragments can bind effectively to the PDH complex.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the pyruvate dehydrogenase complexes from E. coli [8][9][10], from B. stearothermophilus [ 11 ] and from ox kidney [ 12] and ox heart [ 13] by limited proteolysis and electron microscopy suggested that lipoic acid-containing regions of the E2 chains protrude from the E2 core between the E1 and E3 subunits. An extraordinary degree of conformational mobility of large segments of the E2 chains encompassing the lipoyl-lysine residues was demonstrated by proton NMR spectroscopy of the E. coli complex [ 14].…”
Section: Introductionmentioning
confidence: 99%